Dynamic analysis of the integration of electric vehicles in efficient buildings fed by renewables. (1st July 2019) - Buonomano, A.; Calise, F.; Cappiello, F.L.; Palombo, A.; Vicidomini, M.
Highlights: Dynamic simulation model of a novel vehicle to net zero energy building layout. System environmental and thermo economic analysis coupled with electric vehicle. Investigation of the electric vehicle charging effects on the system performance. The system is economically feasible only with a small capacity storage system. Electric vehicle allows one a significant equivalent CO2 emissions reduction. Abstract: This paper analyses the energy, environmental and economic performance of a future scenario where electric vehicles are connected to efficient buildings powered by building integrated flat-plate photovoltaic/thermal collectors, equipped with electric energy storage. The produced renewable electricity and thermal energy are exploited for building electrical and thermal applications. The surplus of produced electricity is stored into the electrical battery and used to charge the electric vehicle. The proposed system is modelled and dynamically simulated within the TRNSYS environment, where special attention is paid to the design of suitable system control strategies, aiming at optimizing the exploitation of the solar energy for electricity and heating purposes. To this aim, a sensitivity analysis is also carried out to find out the optimal system configuration. A case study analysis, relative to the weather zone of Naples (South Italy), is conducted to evaluate the energy, economic and environmental feasibility of the investigated scenario. Simulation results show that, with respect to a reference system, a remarkable reduction of electricity from the grid is achieved, corresponding to a primary energy saving equal to 57.66%. A reduction of 51.63% of CO2 emissions and a simple pay payback period equal to 11.64 years are achieved.